Bromocriptine alone or associated with L-dopa plus benserazide in Parkinson's disease. Issue 12 (December 1977) - Caraceni, T A; Celano, I; Parati, E; Girotti, F
Abstract : Twenty-six patients affected by Parkinson's disease were treated with a 2-Br-alpha-ergocriptine (CB 154): 14 cases were given CB 154 alone, and 12 were given CB 154 along with L-dopa plus benserazide (Madopar). Both CB 154 and combined therapy (CB 154+Madopar) induced a significant improvement in total disability score, tremor, rigidity, akinesia, self-sufficiency, and some motor performance tests (dynamic tests). No significant difference was found between results obtained with CB 154 therapy and with Madopar treatment, while the improvement induced by combined therapy (CB 154+Madopar) was significantly higher than that obtained by Madopar alone. The averse reactions caused by CB 154 alone or associated with Madopar are similar to those observed during other dopaminergic treatment. CB 154 alone or combined with Madopar appears to be a useful advance in the management of Parkinson's disease.